Early‐morning OFF and levodopa dose failures in patients with Parkinson's disease attending a routine clinical appointment using Time‐to‐ON Questionnaire. (28th January 2019) - Stocchi, F.; Coletti, C.; Bonassi, S.; Radicati, F. G.; Vacca, L.
Abstract : Background and purpose: In patients with Parkinson's disease (PD) with motor fluctuations, total daily OFF time is comprised of both end‐of‐dose time and the time taken to turn ON with medication. However, little is known about the impact of delays in ON time. Methods: This was a single‐visit pilot study of fluctuating patients with PD attending a routine appointment. During a single visit, adult patients with idiopathic PD who were treated with levodopa for at least 1 year completed a questionnaire evaluating the time waiting for ON and the symptoms experienced while waiting to turn ON. Patients then completed a 5‐day home time‐to‐ON diary, where they documented how long it took to turn ON following their first morning dose of levodopa in 5‐min increments. Results: A total of 151 consecutive patients completed the study survey, of whom 97 (64.2%) experienced motor fluctuations. Of the patients experiencing motor fluctuations, 54 (56%) reported delays in ON time (latency >30 min) following their first morning dose of levodopa. Half (51%) reported that they had experienced delayed ON at least once in the previous week and 21% reported having delayed ON during all seven mornings of the previous week. In addition, 10% of patients reported having dose failures on four or more mornings during the previous week. The most common symptoms experienced while waiting for ON were slowness (94.8%), fatigue (87.6%), reduced dexterity (82.5%), problems in walking (66.0%) and problems with balance (59.8%). Conclusion: Early‐morning OFF problems such as delays in time to ON and dose failures are common in levodopa‐treated patients with PD.